Vitamin D and Nonskeletal Complications among Egyptian Sickle Cell Disease Patients - Mona Hamdy; Niveen Salama; Ghada Maher; Amira Elrefaee (Advances in Hematology)
Lower levels of vitamin D have been documented in many patients with sickle cell disease (SCD), but data are still inconclusive regarding the association between vitamin D deficiency (VDD) and the occurrence or the severity of various SCD complications. Our study aimed to detect the prevalence of vitamin D deficiency among Egyptian patients with SCD and to associate it with the clinical course of the disease. We measured the level of 25-hydroxy vitamin D in 140 children (age from 4.3 to 15.5years), 80 patients with SCD and 60 controls using enzyme-linked immunosorbent assay. Vitamin D was deficient in 60% of SCD compared to 26.7% of controls. Severe VDD was significantly higher in SCD patients than controls. Patients were divided into 2 groups; Normal group (32 patients) and Deficient group (48 patients). There were statistically significant differences between the 2 groups regarding their age, height percentile, the presence of clinical jaundice, and osseous changes (P values 0.043, 0.024, 0.001, and 0.015, respectively). Hemoglobin and hematocrit values were significantly lower in Deficient group (P values 0.022 and 0.004, respectively) while the levels of aspartate aminotransferase, lactate dehydrogenase, and total and indirect bilirubin were significantly higher in the same group (P values 0.006, 0.001, 0.038, and 0.016, respectively). The frequency of blood transfusions, hospitalization, and vasoocclusive crisis previous year as well as the history of bone fracture and recurrent infections proved to be significantly higher in Deficient group. These findings suggest that VDD may play a role in the pathogenesis of hemolysis and other complication of SCD. Vitamin D monitoring and supplementation in patients with SCD should be implemented as a standard of care to potentially improve health outcomes in these affected patients.